Preparation of a ternary deep eutectic solvent as extraction solvent for dispersive liquid-liquid microextraction of nitrophenols in water samples. Issue 4 (August 2020) - Faraji, Mohammad; Noormohammadi, Farshid; Adeli, Mahnaz
Abstract: A dispersive liquid-liquid microextraction (DLLME) was developed for extraction of 4-nitrophenol (4-NP) and 2, 4-dinitrophenol (2, 4-DNP) in water samples by using a novel ternary hydrophobic deep eutectic solvent (DES) before high performance liquid chromatography determination. Preparation of the DES was done by mixing tetrabutylammonium bromide as acceptor of hydrogen bond and thymol and octanoic acid as donor of hydrogen bondat 60 °C for 5 min. Affecting parameters on extraction were evaluated and optimized. In optimal conditions, calibration curves were linear in the range of 1.0−500 μg L −1 (R 2 ≥ 0.99). The limit of detection (LOD) and limit of quantification (LOQ) was 0.2 and 0.6 μg L −1 for 4-NP and 0.3 and 0.9 μg L -1 for 2, 4-DNP. The intra-day (n = 6) and inter-day (n = 3) precisions at concentration levels of 5.0 and 50 μg L −1 were less than 4.0 % expressed as relative standard deviation. Preconcentration factor was 200 and 180 for 4-NP and 2, 4-DNP, respectively. Finally, applicability of the suggested procedure was investigated via analysis of water samples from different origin (tap, lake and fish pond). Recoveries obtained were acceptable (between 92.5 and 98.7 %).